2009
DOI: 10.1074/jbc.m807042200
|View full text |Cite
|
Sign up to set email alerts
|

Target of Rapamycin (TOR) Mediates the Transduction of Nutritional Signals into Juvenile Hormone Production

Abstract: Anautogeny is a reproductive strategy by which females do not reproduce until they feed. Therefore, nutritional signals must inform the reproductive tissues, and cells that the organism has reached a nutritional status suitable for triggering reproductive processes. One of the possible pathways involved in anautogeny is the "target of rapamycin" (TOR) pathway, which has been described as connecting the nutritional status with growth, proliferation, and cancer. The German cockroach, Blattella germanica, is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 28 publications
11
110
0
Order By: Relevance
“…An in vitro experiment using cultured corpora allata (the glands that produce JH) from Blatella germanica showed that downregulation of TOR leads to reduced JH production (Maestro et al, 2009). Our results take this insight a step forward to establish the interactions between IRS, TOR and JH at an organismal level.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro experiment using cultured corpora allata (the glands that produce JH) from Blatella germanica showed that downregulation of TOR leads to reduced JH production (Maestro et al, 2009). Our results take this insight a step forward to establish the interactions between IRS, TOR and JH at an organismal level.…”
Section: Discussionmentioning
confidence: 99%
“…(Barchuk et al 2007). This model has proven to be useful, and virtually, all interactions have been supported experimentally (Patel et al 2007;Kucharski et al 2008;Maestro et al 2009;Mutti et al 2011). All, that is, except for the confounding data on nervous system development that have been obtained from microarray experiments using whole body samples.…”
Section: Honeybee Diphenism and Caste Differentiationmentioning
confidence: 99%
“…These differences promote the establishment of caste-specific hormonal environments, which in turn drive the expression of different groups of effector genes (Ulrich and Rembold 1983;Hartfelder and Engels 1998;Barchuk et al 2007;Maestro et al 2009;Mutti et al 2011;Moda et al 2013). These may be considered to be the molecular responsible for the development of the initially larger brain seen in queen larvae.…”
Section: Honeybee Brain Development During the Larval Stagementioning
confidence: 99%
“…Application of JH III to these small mosquitoes could initiate vitellogenesis with only one blood meal (15). Recent work in B. germanica also showed that TOR mediated nutrition status affects Vg gene expression and JH levels (16). In lubber grasshoppers, a cumulative feeding threshold is required for vitellogenesis and can be obviated with JH treatment (17).…”
Section: Juvenile Hormone (Jh)mentioning
confidence: 99%
“…D, shown is the time-course of Vg2 mRNA induction by insulin (Ins). Vg2 mRNA levels were measured by qRT-PCR in the fat body isolated from day 2 PAE beetles at 8,16, and 24 h after injection of 100 nl of H 2 O or 10 mg/ml bovine insulin. E, insulin induces Vg2 mRNA even in starved beetles.…”
Section: Juvenile Hormone Work Through the Insulin-like Peptide Signmentioning
confidence: 99%